Menanamkan kesadaran sosial dan ekologis pada siswa sekolah dasar: upaya menuju pendidikan untuk pembangunan berkelanjutan - Ayu Andira; Mayang Rachmawati Adji; Zikri Akbar (Didaktika Dwija Indria, 2026)
This study aims to analyze strategies for instilling social and ecological awareness in elementary school students as part of the implementation of Education for Sustainable Development (ESD). Sustainability awareness is considered important to be formed from an early age considering the increasingly complex global challenges such as environmental damage and social inequality. Using a qualitative approach based on literature review, this study examines the integration of sustainability values in the thematic curriculum, the application of contextual learning approaches (such as PjBL, PBL, experiential, and service learning), and the role of teachers as role models and facilitators of values. Furthermore, it discusses the role of school culture and environment as well as support from national education policies such as the Independent Curriculum and the Pancasila Student Profile. The study results indicate that the success of ESD at the elementary school level is strongly influenced by the synergy between the curriculum, learning methods, teacher capacity, institutional support, and community involvement. This study recommends the importance of strengthening teacher training, providing contextual teaching media, and developing a school culture that supports the internalization of sustainability values in a comprehensive and sustainable manner.